2021
DOI: 10.1111/trf.16220
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood donors' post‐donation symptoms diminish quickly but are discouraging: Results from 6‐day symptom diaries

Abstract: Background: Whole blood donors may experience post-donation symptoms such as fatigue, dizziness, or headache after blood donation, which could influence donor retention. We aimed to examine post-donation symptoms during 1 week after whole blood donation, investigate donor characteristics associated with symptoms, and evaluate associations between symptoms and donor return. Methods: During 1 week, whole blood donors who donated successfully at one of the collection centers in The Netherlands were invited to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our observation that warm glow is stable is consistent with recent reports that warm glow, following blood donation, remains stable over several days 42,68 . However, further studies are needed to measure warm glow over time, both in the lab and in the field, to assess patterns of stability and decay for different types of helping and what predicts any variation in these patterns.…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that warm glow is stable is consistent with recent reports that warm glow, following blood donation, remains stable over several days 42,68 . However, further studies are needed to measure warm glow over time, both in the lab and in the field, to assess patterns of stability and decay for different types of helping and what predicts any variation in these patterns.…”
Section: Discussionsupporting
confidence: 93%
“…Our study employed an online questionnaire to elicit donors' symptoms, and this showed that as reported before, mild symptoms, not noticed or reported by blood bank staff, can have a significant effect on donors' return [3,11,12].…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, some other studies have illustrated no differences in serum calcium levels and age ( Jafari-Giv et al, 2019 ; Endres et al, 1987 ; Jorde, Bonaa & Sundsfjord, 1999 ). In addition, Sweegers et al (2021) also found age was significantly associated with multiple post-donation symptoms (such as fatigue, dizziness, headache and higher energy level) in whole blood donors. Conflicting results also have been reported with respect to the effect of gender on serum calcium levels.…”
Section: Discussionmentioning
confidence: 86%